Dangerous Play: Orcas, Mêtis, and the Global Lockdown - Hardt, Deborah (Humanimalia, 2024)
Since 2020, orcas off the coast of the Iberian Peninsula have been ramming boats with their bodies, causing damage and, in some cases, sinking vessels. To this day, more than 500 incidents have taken place. Scientists are reluctant to call the events intentional acts of aggression and report that what the orcas are doing can be categorized as play. This paper investigates the potential connection between what has been called the “anthropause” that took place during the COVID-19 lockdown and the start of new orca behaviors. It will propose that the orcas are indeed playing but not in the way that has been described by the scientific community. Instead, the orcas are engaging in accordance with the Greek idea of mêtis, a concept that employs a cunning intelligence to outwit strong opponents. I theorize that the orcas are motivated to keep human interference in their waters at bay and use physical violence under the guise of play to achieve this goal, challenging the narrative of human exceptionalism in the process.